Effect of electrolyzed water (EW) in accelerating the cement setting and hydration as demonstrated by the analytical techniques. (13th December 2021) - Mandal, Romio; Panda, Sarat Kumar; Chakraborty, Sumit
Highlights: Use of electrolyzed water (EW) as a greener set accelerator admixture. Determination of cement hydration kinetics in the presence of EW. Evaluation of hydration acceleration effect of EW by analytical techniques. EW influences the early nucleation and flocculation of the hydrated products. A matured and compact microstructure has been developed for EW based cement. Abstract: The present investigation is dealing with the evaluation of setting and hydration performances of cement paste prepared utilizing electrolyzed water (EW). In this study, the effect of EW produced by electrolysis for the different duration (in minutes) was investigated on the setting and hydration behavior of cement paste. It was noticed that the use of EW accelerates the cement hydration reaction and produces more hydrated products at an early age; thereby, an early setting of cement occurs. Analyzing critically, the cement pastes prepared using 1, 3, 7, 15, and 30 min EW show, respectively, the initial and final setting times of cement 63 ± 3, 54 ± 2, 46 ± 2, 38 ± 2, and 29 ± 2 mins (initial) and 160 ± 3, 147 ± 3, 135 ± 3, 122 ± 4, and 108 ± 4 mins (final). Whilst, the distilled water-based cement paste shows the initial and final setting time of cement 70 ± 2 and 172 ± 5 mins, respectively. The quick chemical reaction (hydration) of cement particles in the presence of EW and the formation of more hydrated products at an early age leads to develop a less porous and more compact microstructure as demonstrated by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), mercury intrusion porosity (MIP), and Scanning electron microscopy (SEM) analysis.